2014 International Conference on Advances in Electronics Computers and Communications 2014
DOI: 10.1109/icaecc.2014.7002435
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of ECG sensor for real time signal processing applications

Abstract: This paper describes implementation of ECG Sensor. The system is capable of acquiring and storing patient's ECG data in real-time. This received patient data can be further processed for any real time processing applications. System hardware comprises of micro-controller based ECG acquisition system. Software developed in Visual Basic 6 helps in displaying real time ECG signal. It also stores ECG data at specified location in the form of a text file. This text file data may further be used for any automated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…An electric activity of a heart muscle is measured by placing an electrode at outer surface of the skin, as the heart performing of its function to pump the blood through the circulation system. Electrode is used for sensing bioelectrical potential caused by muscle cells, as a result of mechanical events inside heart muscles are a certain cycle of electrical activity or ECG signal [5], [6]. Thus, electrodes used in this study and location of its placements, to acquire ECG signal as shown in Fig.…”
Section: A Signal Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…An electric activity of a heart muscle is measured by placing an electrode at outer surface of the skin, as the heart performing of its function to pump the blood through the circulation system. Electrode is used for sensing bioelectrical potential caused by muscle cells, as a result of mechanical events inside heart muscles are a certain cycle of electrical activity or ECG signal [5], [6]. Thus, electrodes used in this study and location of its placements, to acquire ECG signal as shown in Fig.…”
Section: A Signal Inputmentioning
confidence: 99%
“…Typically, ECG signal obtained from an electrode was very small amplitude, and ranged around ±2mV, is a very weak signal [5]. Thus, an accurate amplification of ECG signal is a crucial practice, and required to further analysis and displaying a proper ECG waveform.…”
Section: B Signal Conditioningmentioning
confidence: 99%
“…There are many studies using hardware implementation with the aim of helping experts in detecting heart abnormalities quickly. Gawali et al [8] develop a real-time ECG sensor that can acquire and store patient ECG data in real-time. Such patient data can be used for any real-time processing application.…”
Section: Introductionmentioning
confidence: 99%